Rendimiento del Ajonjoli (Sesamum Indicum l,) con dosis de Humus de Lombriz en el fundo Miraflores Banda de Shilcayo-San Martin-Perú - Dionicio Machari, Geoffrey Adolfo (2008)
This paper studies "performance sesame (Sesamum indicum L.) Var. "Creole reque", was executed in Fundo Miraflores property of the Faculty of Agronomy of the Universidad Nacional de San Martin, located in the area of 3.5 kilometers Ahuashiyacu Tarapoto. The design was a (RCBD) with five treatments and four replications respectively. Whose objective was to determine the effect of dose of vermicompost on yield of sesame for which the following observations as started. Plant height at harvest, number of capsules / plant, yield kg / ha benefit analysis / cost. As for performance analysis that scored highest net benefit was the treatment T5 followed by tratamientos.T1, 72, T3 and T4.Esto is due to the interaction of all the nutritional elements that has the vermicompost as nitrogen, phosphorus and potassium, and trace elements are easily assimilated by plants, besides the large number of bacteria, may thanks to enzymes produced by bacteria, combine elements (Camasca, 1994). This Vitorino (1994) adds. Regarding the benefit / cost were lower to the witness, being economical T5 whose benefit cost ratio is 7.7 with a net profit of 5644.73 soles and less economical treatment T4 with a benefit cost ratio of 1.4% with a net profit of 2013.41 soles. Analyzing the results of the cost / benefit of T3 compared to T5 assume that the results of T3 will not make you profitable instantly but the medium and long term, according to (COMPORENSE, 2006) mentions that the residual effect is to 5 years means that it will not make it necessary to apply the following season, will see the return of vermicompost versus control.